Non-isolated high step-up DC/DC converters – An overview - Yavuz Koç (Elsevier, 2022)
High step-up, high efficiency, low cost DC/DC converters have operated as an interface to make use of the renewable energy system generated power. In order to obtain desired output voltage, the DC/AC voltage conversion to AC mains voltage is an important consideration mainly achieved through inverters. Taking into acoount the performance of the non-isolated high step-up DC/DC converters for the renewable energy systems, the substantial amount of topologies studied in past years are the non-isolated high step-up DC/DC converters. Based on proposed and generalized configurations, the non-isolated high step-up DC/DC converters are classified into several categories and reviewed in this paper. So, to clarify the distinguishing solutions, the key features; topological variations, merits and demerits of these converters are discussed and compared. This review work aims to give a well-informed and a well-detailed general framework about these converters and facilitates to derive the new well topologies in the future.